Acute fluid volume changes in men during three days of creatine supplementation - Ziegenfuss, T. N.; Lowery, L. M.; Lemon, P. W. R. (Journal of Exercise Physiology online, 1998)
Despite the plethora of recent research on creatine, little information exists relative to the nature of the weight gain reported from acute (< 5 d) supplementation. This study used multifrequency bioimpedance analysis (MBIA) to estimate the relative changes in total body water (TBW), extracellular (ECV), and intracellular (ICV) fluid volumes in 10 cross-trained and aerobically trained men before, and during three days of creatine monohydrate (Cr) supplementation (0.35 g · kg FFM-1 · d-1). Cr ingestion produced clear trends in fluid shifts, and by day three had increased TBW 2% (0.86 ± 0.68 L, p = 0.07) and ICV 3% (0.77 ± 0.40, p < 0.01); no effect was noted in ECV (p = 0.51). These findings seem to indicate that the weight gain associated with acute Cr supplementation is primarily a result of water retention and that much of this increase is contained within the intracellular compartment.